Organizational health culture in the Korean firefighter intervention studies: a scoping review - Hanbit Jin; Hanbit Jin; Hyungsun Jun; Jisu Ha; Inae Youn; Jungtae Leem; Jungtae Leem; Jungtae Leem (Frontiers in Public Health)
IntroductionThis study examines the current state of intervention studies focused on Korean firefighters, who face unique health challenges due to the demands of their work and specific organizational culture. Recognizing a gap in studies tailored to firefighters’ needs, this scoping review aimed to identify existing interventions and provide recommendations for future research.MethodsFollowing the Joanna Briggs Institute’s methodological guidelines for scoping reviews and the PRISMA-ScR checklist, a seven-stage review was conducted. The search included articles from Korean and international journals published up until January 25, 2024. Data were analyzed using a pre-developed framework and the Template for Intervention Description and Replication checklist. This study was registered on the Open Science Framework (OSF) and is accessible at https://osf.io/s378j/.ResultsFrom 35 articles analyzed, results showed an imbalance in topics, research design, outcome measures, and intervention delivery methods. Additionally, most studies lacked specific focus on firefighters’ unique organizational characteristics and needs.DiscussionThe study highlighted three areas for enhancing intervention research quality: designing and tailoring studies to fit the specific demands of firefighting, ensuring ethical considerations, and aligning with the practical needs of firefighters. Future research should prioritize diverse interventions addressing firefighters’ health, incorporate sensitive and ethical research designs, and work closely with experts in firefighting to develop adaptable and relevant interventions.Systematic Review Registrationhttps://osf.io/s378j/, Registration DOI: https://doi.org/10.17605/OSF.IO/7EQ8M.